Estructura urbana en ciudades fronterizas: Nuevo Laredo-Laredo, Reynosa-McAllen, Matamoros-Brownsville - Corrales Corrales, Salvador (Frontera Norte, 2017)
Eduardo Alarcón Cantú, Tijuana, El Colegio de la Frontera Norte, 2000, 232 pp.